Mucosal Cancers Arising in Potentially Malignant Lesions of the Oral Mucosa Are Marjolin Ulcers: New Insights Into Old Concepts - Guedes, Nycolle Louise; Lourenço, Silvia Vanessa; Nico, Marcello (Dermatology Practical & Conceptual, 2024)
Introduction: Several disparate mucocutaneous diseases present oral mucosal lesions that have been classically labeled as “pre-cancerous,” “pre-malignant,” or “potentially malignant” These include oral lichen planus, dyskeratosis congenita, tertiary syphilitic glossitis chronic graft-versus-host-disease, and oral discoid lupus erythematosus. There is much confusion in literature regarding the real malignant potential of these oral lesions in relation to the incidence of squamous cell carcinoma.Objective: We tried to unify the occurrence of squamous cell carcinoma in some oral mucosal diseases into the classic concept of Marjolin ulcer.Method: We analyzed the most relevant published evidence of the occurrence of squamous cell carcinoma (SCC) arising in oral lichen planus, dyskeratosis congenita, tertiary syphilitic glossitis chronic graft-versus-host-disease, and oral discoid lupus erythematosus, and tried to establish a logical link between them.Results: Reported cases of SCC occurring in oral lesions of these diseases seem to appear in old-standing, scarring lesions.Conclusion: Oral lichen planus, dyskeratosis congenita, tertiary syphilitic glossitis, chronic graft-versus-host-disease, and oral discoid lupus erythematosus are not “pre-malignant diseases,” their long-lasting mucosal scars are prone to the development of SCC. In this sense, this tumor can be considered a mucosal type of Marjolin ulcer.